Association between NAT2, CYP1A1, and CYP1A2 genotypes, heterocyclic aromatic amines, and prostate cancer risk: a case control study in Japan - Masahide Koda; Motoki Iwasaki; Yuko Yamano; Xi Lu; Takahiko Katoh (Komiyama Printing Co. Ltd, 2017)
Abstract Background Heterocyclic aromatic amines (HAAs) may confer prostate cancer risk; however, the evidence is inconclusive and the activity of HAA-metabolizing enzymes is modulated by gene variants. The purpose of our study was to determine whether there was evidence of an association between HAA intake, polymorphisms in NAT2, CYP1A1, and CYP1A2 and prostate cancer risk in Japanese men. Methods Secondary data analysis of an observational case control study was performed. Among 750 patients with prostate cancer and 870 healthy controls, 351 cases and 351 age-matched controls were enrolled for analysis. HAA intake was estimated using a food frequency questionnaire and genotypes were scored by TaqMan real-time PCR assay. Logistic regression analysis was conducted according to affected/control status. Results We found that high HAA intake was significantly associated with an increased risk of prostate cancer (odds ratio (OR), 1.90; 95% confidence interval (95% CI), 1.40-2.59). The increased risk of prostate cancer was observed among individuals with the NAT2 slow acetylator phenotype (OR, 1.65; 95% CI, 1.04-2.61), CYP1A1 GA + GG genotype (OR, 1.27; 95% CI, 1.02-1.59), and CYP1A2 CA + AA genotype (OR, 1.43; 95% CI, 1.03-2.00). In addition, CYP1A1 GA + GG genotypes were associated with increased cancer risk in low (OR, 2.05; 95% CI, 1.19-3.63), moderate (OR, 1.72; 95% CI, 1.07-2.76), and high (OR, 2.86; 95% CI, 1.83-4.47) HAA intake groups. Conclusions Our results suggest that high HAA intake is a risk factor of prostate cancer, and genotypes related to HAA metabolic enzymes can modulate the degree of the risk.